Tera Gymnastics for the Elderly: Community Empowerment in Controlling Hypertension Through Routine Physical Activity in Dusun III, Sidodadi Village, Biru-Biru District, Deli Serdang Regency - Rosaulina, Meta; Manik, Maria Hermita; Sinambela, Megawati; Hasian, Muhammad Tsawaby; Siregar, Ripai (INSTITUT KESEHATAN DELI HUSADA, 2025)
Hypertension is a chronic medical condition in which blood pressure in the arteries increases persistently above normal values, namely ≥140 mmHg for systolic pressure and/or ≥90 mmHg for diastolic pressure. Hypertension is defined as a persistent increase in blood pressure that can be caused by various factors such as age, unhealthy lifestyle, stress, and lack of physical activity. This condition is generally found in the elderly group, due to changes in the function of aging organs and blood vessels. Indonesian Tera Gymnastics is a form of breathing exercise and slow movements, similar to Tai Chi, aimed at improving physical health and relaxation. For people with hypertension, this exercise helps lower blood pressure by improving heart function, breathing, and relaxation. The partners of this community service activity are villagers in Dusun III, Sidodadi Village, Biru-Biru District, Deli Serdang Regency. The method of this community service is counseling and Tera gymnastics. The results of the community service carried out through Tera gymnastics The results of blood pressure measurements carried out before and after the implementation of Tera gymnastics showed a tendency to decrease blood pressure.